(untitled) (World Bulletin of Public Health, 2025)
Periodontal inflammatory diseases are one of the serious and relevant problems of modern dentistry, as there is a steady increase in the incidence of these diseases among young and middle-aged people: more than 50% of people have various clinical manifestations of periodontal pathology by the age of 25-30 (Bakhtimerova O. O., 2016; Blashkova S. L., 2018; Durnovo E. A., 2019; Mizeeva S. M., 2020; Mirsaeva F. Z., 2011). In recent years, there has also been an increase in the prevalence of periodontal diseases with an aggressive, almost continuously recurring course (Bulkina N. V., 2012; Grudyanov A. I., 2017). Features of the development of periodontal pathology and delayed diagnosis lead to the destruction of the human dentition at a young age, psychological and social problems (Bezrukova I. V., 2008; Gazhva S. I., 2013; Gileva O. S., 2013, Zhulev E. N., 2016; Maksimovskaya L. N., 2009). In this regard, it is necessary to improve comprehensive programs for timely diagnosis and treatment of this disease (Averyanov S. V., 2017; Akhmadova M. A., 2016; Barer G. M., 2006; Grigoryan S. S., 2010; Karakov K. G., 2016; Petrova T. G., 2018). The leading etiological factor that triggers the development of inflammatory and destructive periodontal diseases is microbial (Bayakhmetova A. A., 2017; Grigoryan A. S., 2007; Kazarina L. N., 2017; Kruglova N. V., 2015; Romanova A. I., 2017). According to the literature, in addition to the microbial factor, the traumatic, immune, vascular, and local factors also play a special role in the development of periodontal pathology (Alekseenko G. V. 1986). The above-mentioned positions predetermine the need to include drugs that eliminate the negative effects of oral microflora and the consequences of metabolic disorders in periodontal tissues in the complex treatment of rapidly progressive periodontitis, as well as to increase the duration of the disease’s remission